2019
DOI: 10.29080/jhsp.v3i3s.273
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Practices during Pregnancy from the Perspective of Women in Makassar City

Abstract: The practice of breastfeeding during pregnancy is mostly done by women, including in Indonesia. Previous research has reported inconsistencies. Some people claim that this practice is beneficial and others report the risk among mothers, fetus, and breastfed children. The aim of this study is to interpret the practice of breastfeeding during pregnancy from a woman perspective. This study used interpretative phenomenology design with in-depth interviews with seven participants selected purposively. Data were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Some of the research found are outside the context, or not directly related to, breastfeeding such as study on determinants of marrieds' women autonomy affected by the role of kinship norms and the effect of labor force participation on married women's autonomy (Rammohan and Johar, 2009); study on Balinese women's autonomy in making decision regarding their reproductive rights as well as the factors affecting it (Komang Sriningsih, 2017), study on the relation between women's autonomy and their utilisation of antenatal care and the role of family to support women's decision in Primigravida teenagers in rural areas of Central Java (Windha Widyastuti, 2017). However, the following 2 studies are related to mother's autonomy on breastfeeding: 1) Study on mother's perspective towards breastfeeding during pregnancy in Makasar City (Anitasari et al, 2019) . The study indicated that mothers experienced a dilemma to choose between fulfilling infant's right to be given breast milk, as the said best-proven way to have a healthy as well as optimally grown and developed infant, and mother's own thoughts and desire.…”
Section: Literature Review Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the research found are outside the context, or not directly related to, breastfeeding such as study on determinants of marrieds' women autonomy affected by the role of kinship norms and the effect of labor force participation on married women's autonomy (Rammohan and Johar, 2009); study on Balinese women's autonomy in making decision regarding their reproductive rights as well as the factors affecting it (Komang Sriningsih, 2017), study on the relation between women's autonomy and their utilisation of antenatal care and the role of family to support women's decision in Primigravida teenagers in rural areas of Central Java (Windha Widyastuti, 2017). However, the following 2 studies are related to mother's autonomy on breastfeeding: 1) Study on mother's perspective towards breastfeeding during pregnancy in Makasar City (Anitasari et al, 2019) . The study indicated that mothers experienced a dilemma to choose between fulfilling infant's right to be given breast milk, as the said best-proven way to have a healthy as well as optimally grown and developed infant, and mother's own thoughts and desire.…”
Section: Literature Review Theoretical Backgroundmentioning
confidence: 99%
“…The study indicated that mothers experienced a dilemma to choose between fulfilling infant's right to be given breast milk, as the said best-proven way to have a healthy as well as optimally grown and developed infant, and mother's own thoughts and desire. Those thoughts range from intention to cease breastfeeding, perforce breastfeeding attitude, until mother's preference to optimizing care for her pregnancy over fulfilling infant's need to breastfeed (Anitasari et al, 2019). The aforesaid dilemma proven to be a manifestation of mother's incapability in making decision as a result of lacking information and knowledge (Anitasari et al, 2019).…”
Section: Literature Review Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations